GLOBAL TRADE AND AGRICULTURAL ECONOMICS: THE EFFECTS OF PRICE POLICIES AND INTERNATIONAL TRADE AGREEMENTS ON FOOD SECURITY - Fajri Hatim; Ahmed Shah; Sara Hussain (Techno Agriculturae Studium of Research, 2026)
Global trade and agricultural economics play a pivotal role in shaping food security worldwide. Price policies and international trade agreements significantly impact food availability, affordability, and access. This research examines how trade liberalization and protectionist policies affect food security outcomes in various countries, with a focus on the interplay between agricultural price policies and trade agreements. The primary objective of this study is to evaluate the effects of liberalized trade policies and price controls on food security across different regions. A mixed-methods approach was employed, combining quantitative data analysis from global economic databases and qualitative insights from expert interviews. The results indicate that countries with liberalized trade policies and positive trade balances experienced reductions in food insecurity, while protectionist policies did not significantly improve food security, despite price control measures. The study highlights that trade liberalization, when paired with effective price stabilization, leads to improved food security. Conversely, protectionism tends to exacerbate food insecurity by limiting access to affordable food and increasing market volatility. This research emphasizes the need for a balanced approach to trade and price policies in fostering global food security.